Perbedaan Status Gizi Dan Lama Hari Sakit Pada Bayi AsiEksklusif Dan Non Eksklusif Di Puskesmas PucangsawitKota Surakarta - Fazriyaa, Israul, Susi Dyah P, M.Si, Rustiningsih, S.KM.,M.Kes (2015)
Introduction: Since were born until after several months old, babies are not able to establish a complete immune system by their own. Breastmilk provides immune substances that cannot be made by babies, so babies will be less frequently ill when they are breast-fed. The anti-infective agents in breastmilk protect babies from various kinds of infections, whether caused by bacteria, viruses, and other antigens. Breastmilk contains complete nutrients compares with formula milk. Thus, breastmilk affects nutrional status of babies. Objective: This study aimed to find the differences of nutritional status and duration of illness between exclusive breast-fed and non-exclusive breast-fed babies in Public Heath Center of Pucangsawit, Surakarta. Methods: This study was an observational study with cross sectional design with a number of 104 respondents. Data on nutritional status were obtained using body weight-for-age index through interview for 4 weeks; counted in day(s), and taken four times in a month (once a week). Statistical analysis used Independent t-test and Mann Whitney. Results: Nutritional status of all exclusive breast-fed babies was good while 98,1% non-exclusive breast-fed babies was good (p = 0.00). The exclusive breast-fed babies who had skort duration of illness was 63,5%. While 63,5% of non-exclusive breast-fed babies had long duration of illness. Conclusion: There was difference in the nutritional status between the exclusive breast-fed and the non-exclusive breast-fed babies in Public Health Center Pucangsawit. There was a difference in the duration of illness between the exclusive breast-fed and non-exclusive breast-fed babies in Public Health Center Pucangsawit.